A randomized evaluation of the TriGuard™ HDH cerebral embolic protection device to Reduce the Impact of Cerebral Embolic LEsions after TransCatheter Aortic Valve ImplanTation: the REFLECT I trial. (17th May 2021) - Lansky, Alexandra J; Makkar, Rajendra; Nazif, Tamim; Messé, Steven; Forrest, John; Sharma, Rahul; Schofer, Joachim; Linke, Axel; Brown, David; Dhoble, Abhijeet; Horwitz, Phillip; Zang, Ming; et al.
Abstract: Aims : The REFLECT I trial investigated the safety and effectiveness of the TriGuard™ HDH (TG) cerebral embolic deflection device in patients undergoing transcatheter aortic valve replacement (TAVR). Methods and results : This prospective, multicentre, single-blind, 2:1 randomized (TG vs. no TG) study aimed to enrol up to 375 patients, including up to 90 roll-in patients. The primary combined safety endpoint (VARC-2 defined early safety) at 30 days was compared with a performance goal. The primary efficacy endpoint was a hierarchical composite of (i) all-cause mortality or any stroke at 30 days, (ii) National Institutes of Health Stroke Scale (NIHSS) worsening at 2–5 days or Montreal Cognitive Assessment worsening at 30 days, and (iii) total volume of cerebral ischaemic lesions detected by diffusion-weighted magnetic resonance imaging at 2–5 days. Cumulative scores were compared between treatment groups using the Finkelstein–Schoenfeld method. A total of 258 of the planned, 375 patients (68.8%) were enrolled (54 roll-in and 204 randomized). The primary safety outcome was met compared with the performance goal (21.8% vs. 35%, P  < 0.0001). The primary hierarchical efficacy endpoint was not met (mean efficacy score, higher is better: −5.3 ± 99.8 TG vs. 11.8 ± 96.4 control, P  = 0.31). Covert central nervous system injury was numerically lower with TG both in-hospital (46.1% vs. 60.3%, P  = 0.0698) and at 5 days (61.7 vs. 76.2%, P  = 0.054) compared with controls. Conclusion : REFLECT I demonstrated that TG cerebral protection during TAVR was safe in comparison with historical TAVR data but did not meet the predefined effectiveness endpoint compared with unprotected TAVR controls. Graphical Abstract: